2023
DOI: 10.3390/pathogens12020315
|View full text |Cite
|
Sign up to set email alerts
|

High Burden of Co-Infection with Multiple Enteric Pathogens in Children Suffering with Diarrhoea from Rural and Peri-Urban Communities in South Africa

Abstract: Infectious diarrhoea contributes to high morbidity and mortality in young children from sub-Saharan Africa. The aim of this study was to assess the prevalence of single and multiple diarrhoeal-causing pathogen combinations in children suffering from diarrhoea from rural and peri-urban communities in South Africa. A total of 275 diarrhoea stool specimens were collected between 2014 and 2016 from Hospitals and Primary Health Care clinics. The BioFire® FilmArray® Gastrointestinal panel was used to simultaneously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 77 publications
0
5
1
Order By: Relevance
“… 80 Likewise, in the present study, 2 or 3 enteric bacterial pathogens (co-infection, co-occurrence) were found in 8.53% diarrheic UFC and 6.02% of their human contacts. The enteric bacterial coinfection rates is higher than the reports of Cho et al, 6 and lower than the finding of Potgieter et al 81 who recently reported, 1.43% and 29% from Gyeongju, Korea, and South Africa, respectively. In agreement to the present study, Andersson et al 82 and Zhang et al 80 also reported enteric bacterial coinfection in diarrheic and nondiarrheic individuals with higher occurrence rates in diarrheal cases.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“… 80 Likewise, in the present study, 2 or 3 enteric bacterial pathogens (co-infection, co-occurrence) were found in 8.53% diarrheic UFC and 6.02% of their human contacts. The enteric bacterial coinfection rates is higher than the reports of Cho et al, 6 and lower than the finding of Potgieter et al 81 who recently reported, 1.43% and 29% from Gyeongju, Korea, and South Africa, respectively. In agreement to the present study, Andersson et al 82 and Zhang et al 80 also reported enteric bacterial coinfection in diarrheic and nondiarrheic individuals with higher occurrence rates in diarrheal cases.…”
Section: Discussioncontrasting
confidence: 56%
“…Children in LICs might be exposed simultaneously to multiple enteric pathogens due to poor sanitary conditions in the environment, and poor quality of food and drinking water contributing to the widespread of microorganisms. 80,81,83,84 The study result also showed the overall occurrence rate of the diarrheagenic FBPs was linearly increasing from December 2021 to February 2022 (winter) and June to August (summer) with peaks of 73.91% and 45.45%, in February and July, respectively (Figure 2A). Pediatric diarrheal disease is caused by a wide variety of pathogens and various studies have found that some pathogens are seasonal, peaking at different times of the year.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Co-detection between bacteria and viruses was confirmed in 47% of cases. Similarly, a study conducted in South Africa to determine the prevalence of individual and multiple diarrhoea-causing pathogen combinations among children suffering from diarrhoea in rural and peri urban communities reported a 47% prevalence of bacterial and viral co-infection [ 77 ]. The prevalence of co-detection between NoV (GI/GII) and DEC as well as RV-A and DEC in this study was higher than that in Southwest China (25.3% versus 1.1% and 25.3% versus 2.3%, respectively) [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Burundi, after malaria and pneumonia, diarrhea was the third leading cause of mortality among children under 5 years old with an estimated mortality of seven deaths per 1,000 live births (8). Up to 55% coinfection with multiple gastrointestinal bacteria including diarrheagenic E. coli and Shigella isolates was reported in children under the age of ve years suffering from diarrhea in South Africa (9).…”
Section: Introductionmentioning
confidence: 99%